Sick leave, disability, and mortality in acute hepatic porphyria: a nationwide cohort study - Carl Michael Baravelli; Aasne Karine Aarsand; Sverre Sandberg; Mette Christophersen Tollånes (Orphanet Journal of Rare Diseases, 2020)
Abstract Background Acute hepatic porphyria (AHP) consists of three rare metabolic disorders. We investigated the risk of long-term sick leave, disability pension, and premature death in individuals with AHP compared to the general population. Methods In a nationwide cohort study from 1992 to 2017, records of 333 persons (total person-years = 6728) with a confirmed AHP diagnosis were linked to several national compulsory registries (reference population = 5,819,937). We conducted survival analyses to assess additional risk. Results Persons with AHP had higher risks of accessing long-term sick leave (adjusted hazard ratio (aHR): 1.5, 95% confidence interval (CI): 1.3, 1.7) and disability pension (aHR: 1.9, CI: 1.5, 2.4). The risk was highest in persons who had been hospitalised for acute attacks, while no additional risk was observed in asymptomatic AHP gene mutation carriers. The median age when accessing disability pension was 45 years, 21 years younger than the general population. AHP was associated with increased risk of mortality due to hepatocellular carcinoma (adjusted mortality rate ratio (aMRR): 84.4, CI: 37.8, 188.2), but no overall increased risk of premature death was observed. Conclusions Persons with symptomatic AHP were at increased risk of accessing long-term sick leave and disability pension but not of premature death.